Organizational Investment and Employee Reciprocity of Real Estate Companies: Basis for Action Plan - Berina Jr., Elano R. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examines the relationship between organizational investment and employee reciprocity in small and medium-sized real estate companies in Calamba, Laguna. Rooted in Blau’s Social Exchange Theory (1964), the research explores how leadership, recognition, and career development—as forms of organizational investment—affect employee engagement, loyalty, and productivity, which are key indicators of employee reciprocity. Employing a descriptive-correlational research design, data were gathered from 60 respondents through a validated survey instrument. The results revealed that both organizational investment and employee reciprocity are perceived at a high level by employees. A statistically significant relationship was identified between the two variables, indicating that when organizations invest in their people, employees are more likely to respond with increased commitment, productivity, and loyalty. Additionally, demographic factors such as age, educational background, and length of service showed some influence on how investment and reciprocity were perceived. The study underscores the critical role of strategic investment in leadership development, employee recognition, and structured career pathways in enhancing workplace culture and performance. These findings offer practical insights for business leaders and HR practitioners to design effective investment strategies that foster a culture of reciprocity, ultimately contributing to long-term organizational stability and competitiveness in the real estate sector. An action plan was proposed based on the results to guide companies in strengthening their workforce through targeted initiatives.